Penyuluhan dan Pemberian Video Edukasi Penggunaan Sunscreen Pada Kalangan Remaja - jannah, nadia miftahul; Vifta, Rissa Laila (Politeknik Indonusa Surakarta, 2025)
Sunlight plays an important role in the formation of vitamin D, bones, and teeth. However, continuous exposure to UV rays has adverse effects on healthy skin. The Semarang area, Central Java is an area with a tropical climate that has high sunlight intensity. This is the basis for the use of sunscreen when doing activities indoors and outdoors. Sunscreen or sunscreen is a preparation that can reflect or absorb UV rays. The use of sunscreen since adolescence aims to protect the skin from UV exposure, and efforts to prevent premature aging and skin cancer. However, adolescents' knowledge about the types of UV rays, types of sunscreens, and the selection of SPF sunscreens that can be used for daily activities is still limited. Providing counseling and education related to sunscreen can be done as an effort to prevent the harmful effects of UV rays. The activity was carried out on students of SMA Muhammadiyah Gubug in October 2024. The instrument in providing the material was a PowerPoint containing educational materials and videos, while the Google Form platform was used to conduct the pre-test and post-test. The results of this community service showed an increase in students' knowledge of sunscreen use as seen from the pre- and post-test scores. The results showed an increase in respondents' knowledge (35%) before and after providing the material, so it can be said that the counseling and education were successful in increasing knowledge.